Gut dysbiosis mediates the association between antibiotic exposure and chronic disease - Guarner, Francisco; Bustos Fernandez, Luis; Cruchet, Sylvia; Damião, Adérson; Maruy Saito, Aldo; Riveros Lopez, Juan Pablo; Rodrigues Silva, Luciana; Valdovinos Diaz, Miguel Angel (Frontiers in Medicine, 2024)
Antibiotics are safe, effective drugs and continue to save millions of lives and prevent long-term illness worldwide. A large body of epidemiological, interventional and experimental evidence shows that exposure to antibiotics has long-term negative effects on human health. We reviewed the literature data on the links between antibiotic exposure, gut dysbiosis, and chronic disease (notably with regard to the “developmental origins of health and disease” (“DOHaD”) approach). Molecular biology studies show that the systemic administration of antibiotic to infants has a rapid onset but also often a long-lasting impact on the microbial composition of the gut. Along with other environmental factors (e.g., an unhealthy “Western” diet and sedentary behavior), antibiotics induce gut dysbiosis, which can be defined as the disruption of a previously stable, functionally complete microbiota. Gut dysbiosis many harmful long-term effects on health. Associations between early-life exposure to antibiotics have been reported for chronic diseases, including inflammatory bowel disease, celiac disease, some cancers, metabolic diseases (obesity and type 2 diabetes), allergic diseases, autoimmune disorders, atherosclerosis, arthritis, and neurodevelopmental, neurodegenerative and other neurological diseases. In mechanistic terms, gut dysbiosis influences chronic disease through direct effects on mucosal immune and inflammatory pathways, plus a wide array of direct or indirect effects of short-chain fatty acids, the enteric nervous system, peristaltic motility, the production of hormones and neurotransmitters, and the loss of intestinal barrier integrity (notably with leakage of the pro-inflammatory endotoxin lipopolysaccharide into the circulation). To mitigate dysbiosis, the administration of probiotics in patients with chronic disease is often (but not always) associated with positive effects on clinical markers (e.g., disease scores) and biomarkers of inflammation and immune activation. Meta-analyses are complicated by differences in probiotic composition, dose level, and treatment duration, and large, randomized, controlled clinical trials are lacking in many disease areas. In view of the critical importance of deciding whether or not to prescribe antibiotics (especially to children), we suggest that the DOHaD concept can be logically extended to “gastrointestinal origins of health and disease” (“GOHaD”) or even “microbiotic origins of health and disease” (“MOHaD”).